Scientific Opinion on the safety and efficacy of Danisco Xylanase 40000 G/L (endo‐1, 4,‐beta‐xylanase) for laying hens and poultry minor species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal)
Abstract Danisco Xylanase 40000 G/L is a feed additive that contains endo‐1, 4‐beta‐xylanase produced by a genetically modified strain of Trichoderma reesei. The additive is intended for use in minor poultry species. The applicant is also seeking a modification of the current authorisation for laying hens (reduction of the minimum dose). The additive is intended for use in laying hens and minor poultry species at a dose range of 625–2 500 U/kg complete feedingstuffs. The efficacy and safety of this product for the target species, consumer, user and the environment, as well as the safety aspects of the genetic modification, were previously assessed by the EFSA. The solid and liquid forms of the product are considered to be equivalent in terms of efficacy and safety for the target animal. Based on the data from three tolerance studies with major poultry species, the FEEDAP Panel concludes that Danisco Xylanase is safe for all minor poultry species (fattening and laying) at the maximum recommended dose (2 500 U/kg complete feed). The FEEDAP Panel considers, based on the results of a meta‐analysis of five trials, that Danisco Xylanase at the new proposed minimum dose of 625 U/kg complete feed has the potential to be efficacious in laying hens. Since the additive has shown to be effective at the minimum dose of 625 U/kg in the major poultry species, and considering that the mode of action of xylanases can be reasonably assumed to be the same in all poultry species, the conclusions on efficacy for major poultry species can be extrapolated to all minor poultry species (fattening and laying) at the dose of 625 U/kg complete feed.